Multi-disciplinary approach to identifying Native American impacts on Late Holocene forest dynamics in the southern Sierra Nevada range, California, USA. (September 2016) - Klimaszewski-Patterson, Anna; Mensing, Scott A.
Graphical abstract: Abstract: Fire is a natural disturbance component and driver of forest composition in the western United States. Cooler/wetter climates are typically associated with less frequent fires and succession of montane forests to more shade-tolerant, fire-sensitive taxa. Native Americans have lived in California since the terminal Pleistocene and used fire to alter the landscape and maximize natural resources. Determining the extent and impact of anthropogenic burning on California's landscape is difficult; however, because the archaeological record is mostly silent on the subject. The region's ethnographies also mention the practice from a prehistoric context only in passing. Here, we show that comparing the prevalence of fire-sensitive to fire-adapted taxa in the pollen record can help distinguish periods when vegetation does not respond as expected to climate change. We argue that the prevalence of shade-intolerant/fire-adapted taxa during climatically cool, wet periods such as the Little Ice Age provide evidence for anthropogenic burning. At Holey Meadow, in Sequoia National Forest, we find strong evidence for a Native American influenced landscape from 750 to 100 cal yr BP. We also see a strong anthropogenic effect on modern vegetation following European settlement in A.D. 1854, a period marked by a precipitous decline in traditional tribal use of the area and the inception of modern fire exclusion policies. These results indicate that anthropogenic impacts on forest composition can be distinguished from climatic drivers through the use of paleoenvironmental proxies. They further indicate that anthropogenic burning helped structure Late Holocene southern Sierra Nevada biomes.